SAT0549 Methotrexate Versus Mycophenolate Mofetil in Neurosarcoidosis: A Retrospective Trial. (9th June 2015) - Bitoun, S.; Cohen Aubart, F.; Haroche, J.; Mathian, A.; Hie, M.; Boutin, T.H.D.; Arnaud, L.; Bouvry, D.; Borie, R.; Sacre, K.; Mahevas, M.; Hausfater, P.; et al.
Abstract : Background: Sarcoidosis is a multi-systemic granulomatous disease of unknown cause in which neurological involvement is rare. Corticosteroids remain first line treatment even though immunosuppressive therapy is increasingly prescribed as steroid-sparing agent. Objectives: To compare efficiency and safety of methotrexate versus mycophenolate mofetil use to treat neurological involvement of sarcoidosis. Methods: A multicentric retrospective study was performed between 2010 and 2014. Inclusion criteria were: Histologically proven sarcoidosis after exclusion of differential diagnosis, central or peripheral neurologic involvement and prescription of mycophenolate mofetil (MMF) or methotrexate (MTX) for at least one month. Steroid tapering was achieved by local physician habits. The main outcome was the time to relapse. Relapse was defined as the necessity to increase steroids by at least 20 mg per day. Secondary outcomes were safety and switch to second line immunosuppressive therapy. Results: Forty-six patients were included, 14 in the MMF group and 32 in the MTX group. There were 29 males and 17 women. Median age at diagnosis was 38.5 years old range (11-76). Topography of neurological involvements was the brain (27 patients), the cranial nerves (21 patients), the meninges (18 patients), the spinal cord (9 patients), the radiculae (4 patients), the peripheral nerves (4 patients) and the muscle (3 patients). Median follow-up was 84 months. Seventy nine percent of patients relapsed in the MMF group versus 46% in the MTX group. The time to relapse was 11 months in the MMF group vs 28 months in the MTX group. In the survival analysis time to relapse in the MMF group was significantly lower than in the MTX group (p=0.0491). Among relapsing patients 7 (70%) in the MMF group and 13 (87%) in the MTX group required second in immunosuppressive therapy. There was less minor infectious side effects in MMF group 0% than in the MTX 19% group p=0.02. Conclusions: Methotrexate therapy seems to be more efficient in preventing relapse in neurosarcoidosis than mycophenolate mofetil. Safety was good in both groups but with less minor infections in the MMF group. Theses results need to be confirmed in a randomized controlled trial. Disclosure of Interest: None declared